2015
DOI: 10.3390/ma9010014
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectrics under the Synchrotron Light: A Review

Abstract: Currently, an intensive search for high-performance lead-free ferroelectric materials is taking place. ABO3 perovskites (A = Ba, Bi, Ca, K and Na; B = Fe, Nb, Ti, and Zr) appear as promising candidates. Understanding the structure–function relationship is mandatory, and, in this field, the roles of long- and short-range crystal orders and interactions are decisive. In this review, recent advances in the global and local characterization of ferroelectric materials by synchrotron light diffraction, scattering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 131 publications
3
14
0
Order By: Relevance
“…The fraction of the ferroelectric R3c symmetry in BNBT6 ceramics increases after application of an electric field at the expense of the Pm-3m cubic symmetry [31]. That is, the short-range polar order (nanodomains) of the globally non-polar component of the material becomes a long-range polar order (macroscopic ferroelectric domains) under the action of the electric field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fraction of the ferroelectric R3c symmetry in BNBT6 ceramics increases after application of an electric field at the expense of the Pm-3m cubic symmetry [31]. That is, the short-range polar order (nanodomains) of the globally non-polar component of the material becomes a long-range polar order (macroscopic ferroelectric domains) under the action of the electric field.…”
Section: Resultsmentioning
confidence: 99%
“…However, the coexistence of ferroelectric rhombohedral R3c and ferroelectric tetragonal P4mm is well documented at the tetragonal edge of the 0.08 < x < 0.11 [15]. Besides, the wide peaks at the low-angle side of the strong perovskite peaks (marked with arrows in Figure 6) disappear after powdering the poled samples, thus indicating that this is a structural feature related to a surface structure [31] but not to the coexistence of ferroelectric phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, advanced diffraction experiments on polycrystalline ceramics have elucidated several electric field and/or stress-induced structural mechanisms that are unique to Pb-free piezoelectrics. A review of these developments can be found in references [41,42]. Nevertheless, similar reviews on single-crystal diffraction experiments of Pb-free piezoelectrics are absent.…”
Section: Crystallographic Phase Transitionmentioning
confidence: 99%
“…The crystallographic structural changes can be characterized from data collected in a diffraction experiment by monitoring changes in some essential features, such as hkl diffraction peak position to determine changes in lattice planes spacing and splitting of hkl reflections to identify changes in crystallographic symmetry. In addition, change in intensities of hkl reflections can reflect various crystallographic and microstructural changes such as relative positions of different ions, state of microstructural defects, as well as internal strains, which can be distinguished based on quantitative modeling [36,37,[41][42][43][44].…”
Section: Crystallographic Phase Transitionmentioning
confidence: 99%